About the growth of knowledge - McLean, Alan (2006)
This paper discusses and evaluates diverse conceptions of knowledge current in the emerging discipline of knowledge management. These include: the idea of knowledge stored digitally; personal knowledge; the DIKW knowledge pyramid; team learning and organisational learning.The author contends that speaking coherently about the growth of knowledge is impossible without first recognising a group of unresolved problems in the theory of knowledge.These include the question of what qualifies as knowledge and the related question of which entities are able to possess knowledge.Rather that trying to settle these questions, the author examines diverse conceptions of knowledge and discusses their implications for the question of tracking knowledge growth.The paper is relevant to practitioners who manage intellectual resources or support learning. The paper includes suggestions relating to empirical research and theoretical development in knowledge management and the theory of knowledge.